HPLC method for determination of in vitro delivery through and into porcine skin of adefovir (PMEA) - Vávrová, Kateřina; Lorencová, Kateřina; Klimentová, Jana; Novotný, Jakub; Hrabálek, Alexandr (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2007)
A simple HPLC/UV method for the determination of the transdermal permeation and dermal penetration of a broad-spectrum antiviral drug adefovir (PMEA) was developed. The separation was achieved on a C18 column with the mobile phase composed of 10 mM KH2PO4 and 2 mM Bu4NHSO4 at pH 6.0 and 7% acetonitrile. The method was validated with respect to selectivity, linearity (0.1-50 microg/ml), precision, accuracy, and stability. Transdermal permeation of 2% PMEA was studied in vitro using the Franz diffusion cell and porcine skin. The flux values were 1.8, 3.0, and 0.6 microg/cm2/h from aqueous donor samples at pH 3.4 and 7.4, and isopropyl myristate, respectively. The respective skin concentrations at 48 h were 294, 263, and 971 microg/g from these vehicles. These results will serve as a lead for further studies on transdermal and topical delivery of antivirals from the group of acyclic nucleoside phosphonates.
Keywords: zvířata; Skin; Chromatography, High Pressure Liquid; In Vitro Techniques; adenin; organofosfonáty; Reproducibility of Results; Animals; prasata; vysokoúčinná kapalinová chromatografie; financování organizované; Financing, Organized; Organophosphonates; Antiviral Agents; antivirové látky; kůže; aplikace kožní; kožní absorpce; Spectrophotometry, Ultraviolet; spektrofotometrie ultrafialová; techniky in vitro; Skin Absorption; Administration, Cutaneous; reprodukovatelnost výsledků; Swine; Adenine